Oxidative stress and mitochondrial damage: importance in non-SOD1 ALS - Carrì, Maria Teresa; Valle, Cristiana; Bozzo, Francesca; Cozzolino, Mauro (Frontiers in Cellular Neuroscience, 2015)
It is well known that mitochondrial damage is both the major contributor to oxidative stress (the condition arising from unbalance between production and removal of reactive oxygen species) and one of the major consequences of oxidative stress, because of the high dependence of mitochondrial function on redox-sensitive targets such as intact membranes. Conditions in which neuronal cells are not able to cope with mitochondrial damage and oxidative stress seem to lead or contribute to several neurodegenerative diseases including Amyotrophic Lateral Sclerosis (ALS), at least in the most studied SOD1-linked genetic variant. As summarized in this review, new evidence indicates that mitochondrial damage and oxidative stress play a role also in non-SOD1 ALS and thus they may represent a target for therapy despite previous failures in clinical trials.